Spacing between plants and doses of nitrogen and potassium in fertigated seedless watermelon - Feltrim, Anderson Luiz; Cecílio Filho, Arthur Bernardes; Gonsalves, Marcus Vinicius; Pavani, Luiz Carlos; Barbosa, José Carlos; Mendoza Cortez, Juan Waldir (Pesquisa Agropecuária Brasileira, 2011)
The objective of this work was to evaluate the effects of N and K2O doses, applied by a drip fertigation system, and of distances between plants on the productivity of the Shadow hybrid of seedless watermelon. The experiment was carried out from August to October 2008, at Tupã, SP, Brazil. Four doses of N + K2O (79.8 + 106.7, 106.4 + 142.2, 133.0 + 177.7, and 159.6 + 213.2 kg ha-1) and four spacings between plants (0.5, 1.0, 1.5, and 2.0 m) were evaluated in 2.0-m spaced rows. A randomized complete block design with split plots and three replicates was used. Evaluated variables were: N and K foliar content, mean fruit weight, number of fruit and total and commercial productivity; and number of fruit from classes 3 to 5 kg, 5 to 7 kg, 7 to 9 kg, and above 9 kg per plant and per hectare. Nitrogen and potassium doses significantly affected K foliar content, and total and commercial productivity of the hybrid Shadow decreased linearly with the increase in spacing between plants. However, there was no effect of the interaction between factors or from the factors themselves on the other evaluated variables.